Characterization of microglia/macrophage phenotypes in the spinal cord following intervertebral disc herniation - Kühl, Bianca; Beyerbach, Martin; Baumgärtner, Wolfgang; Gerhauser, Ingo (Frontiers in Veterinary Science, 2022)
Dogs frequently suffer from traumatic spinal cord injury (SCI). Most cases of SCI have a favorable prognosis but 40-50% of dogs with paraplegia and absence of nociception do not regain ambulatory abilities, eventually leading to euthanasia. Microglia and infiltrating macrophages play a crucial role in inflammatory process after SCI. However, little is known about microglia/macrophage phenotypes representing a potential target for future therapeutic strategies. In the present study, the microglia/macrophage phenotype was characterized by immunohistochemistry in the morphologically unaltered canine spinal cord (10 control dogs) and during acute and subacute SCI (1-4 and 5-10 days post injury, 9 and 8 dogs, respectively) using antibodies directed against IBA1, MAC387, MHC-II, lysozyme, EGR2, myeloperoxidase, CD18, CD204 and lectin from Griffonia simplicifolia (BS-1). The expression of these markers was also analyzed in the spleen as reference for the phenotype of histiocytic cells. Histological lesions were absent in controls. In acute SCI, 4 dogs showed mild to moderate hemorrhages, 2 dogs bilateral gray matter necrosis and 6 dogs mild multifocal axonal swellings and myelin sheath dilation. One dog with acute SCI did not show histological alterations except for few dilated myelin sheaths. In subacute SCI, variable numbers of gitter cells, axonal changes and dilated myelin sheaths were present in all dogs and large areas of tissue necrosis in 2 dogs. Neuronal chromatolysis was found in 3 dogs with acute and subacute SCI, respectively. In control dogs, microglia/macrophage constitutively expressed IBA1 and rarely other markers. In acute SCI, a similar marker expression was found except for an increase in MAC387-positive cells in the spinal cord white matter due to an infiltration of few blood-borne macrophages. In subacute SCI, increased numbers of microglia/macrophages expressed CD18, CD204 and MHC-II in the gray matter SCI indicating enhanced antigen recognition, processing and presentation as well as cell migration and phagocytosis during this stage. Interestingly, only CD204-positive cells were upregulated in the white matter, which might be related to gray-white matter heterogeneity of microglia as previously described in humans. The present findings contribute to the understanding of the immunological processes during SCI in a large animal model for human SCI.